The implementation of Jesus' transformative leadership in leaders and activists of the Protestant Christian church in Bali, Indonesia - I Ketut Darsana; Muner Daliman; Suwarsono Warnomartoyo; Sri Wahyuni; Jamin Tanhidy (Center for Humanities and Innovation Studies, 2021)
Jesus Christ is a role model for leaders, with His leadership still relevant until now. Jesus brought transformation to His community, and this transformative leadership model is needed to renew church ministry and evangelism. This article aims to find out the level of implementation of Jesus' transformative leadership among church leaders and activists of the Protestant Christian Church in Bali (GKPB) at Denpasar. This “traditional” church needs transformation to improve its quality and range of services outside Bali Island. The research used a quantitative method by measuring the Four Dimensions (D) in the concept of transformative leadership of Jesus according to the Gospel of Matthew. Results show that first, the implementation of Jesus' transformative leadership among GKPB Denpasar leaders and activists was found to be in